Connect with English - McPartland-Fairman, Pamela (McGraw-Hill, 1998)
Emphasizes listening comprehension skills and helps students gain an understanding of the characters and the events in the "Connect With English" story. This title also covers additional skills and topics such as reading, writing, speaking, culture, and vocabulary development